Combining Intra- and Interindividual Approaches in Epistemic Beliefs Research - Rosman, Tom; Seifried, Eva; Merk, Samuel (Frontiers in Psychology, 2020)
We combined inter- and intraindividual approaches to investigate university students’ biology- and psychology-specific specific epistemic beliefs (beliefs about the nature and structure of knowledge). We expected that university students would perceive the discipline of biology as more absolute and less multiplistic than the discipline of psychology (intraindividual perspective). Furthermore, we expected students from so-called ‘hard’ disciplines to perceive biology as more absolute and less multiplistic than students from soft disciplines (interindividual perspective). Finally, we expected that students from hard disciplines, compared to their peers from soft disciplines, would perceive stronger differences between biology and psychology (combined perspective). Hypotheses were tested, using Bayes factors, in N = 938 university students from a multitude of disciplines. Results revealed that university students perceive biology as considerably more absolute and less multiplistic compared to psychology. However, the findings also suggest that there are no strong interindividual differences between students from hard and soft disciplines regarding the perception of biology. Finally, results revealed that students enrolled in harder disciplines perceive a slightly stronger difference between biology and psychology. In sum, intraindividual effects were considerably stronger, which elicits doubt that students from hard disciplines espouse a fundamentally different set of epistemic beliefs than their peers from soft disciplines.